Helios Expression Is Downregulated on CD8+ Treg in Two Mouse Models of Lupus During Disease Progression - París-Muñoz, Andrés; Aizpurua, Gonzalo; Barber, Domingo F. (Frontiers in Immunology, 2022)
T cell mediated autoimmunity reflects an imbalance in this compartment that is not restored by tolerogenic immune cells, e.g., regulatory T cells or tolerogenic dendritic cells (tolDCs). Although studies into T cell equilibrium have mainly focused on regulatory CD4+FoxP3+ T cells (CD4+ Tregs), recent findings on the lesser known CD8+ Tregs (CD44+CD122+Ly49+) have highlighted their non-redundant role in regulating lupus-like disease and their regulatory phenotype facilitated by the transcription factor Helios in mice and humans. However, there are still remaining questions about Helios regulation and dynamics in different autoimmune contexts. Here, we show the absence of CD8+ Tregs in two lupus-prone murine models: MRL/MPJ and MRL/lpr in comparison with a non-prone mouse strain like C57BL/6. We observed that all MRL animals showed a dramatically reduced population of CD8+ Tregs and a greater Helios downregulation on diseased mice. Helios induction was detected preferentially on CD8+ T cells from OT-I mice co-cultured with tolDCs from C57BL/6 but not in MRL animals. Furthermore, the Helios profile was also altered in other relevant T cell populations implicated in lupus, such as CD4+ Tregs, conventional CD4+ and double negative T cells. Together, these findings could make Helios a versatile maker across the T cell repertoire that is capable of differentiating lupus disease states.